Application of Cornelian Cherry (Cornus mas L.) Peel in Probiotic Ice Cream: Functionality and Viability during Storage - Shaghayegh Haghani; Milad Hadidi; Shiva Pouramin; Fateme Adinepour; Zahra Hasiri; Andrés Moreno; Paulo E. S. Munekata; José M. Lorenzo (Antioxidants, 2021)
In this study, cornelian cherry (Cornus mas L.) peel (CCP) was incorporated into a probiotic ice cream formulation containing Bifidobacterium lactis to investigate the potential effect of CCP on the viability of B. lactis in the ice cream after simulated gastrointestinal stress and during 120 days of storage. Furthermore, the effect of the addition of CCP (3, 6, and 9%) on bioactive compounds, antioxidant activity, and physicochemical and sensory attributes of the ice cream was evaluated. The results showed that the addition of CCP significantly enhanced vitamin C, total polyphenols, total anthocyanin content, and antioxidant activity of the ice cream. During frozen storage of the ice cream, phenolic compounds and anthocyanins were quite stable, but vitamin C significantly decreased. The addition of CCP had no significant effect on the viability of B. lactis throughout the freezing process, but increments of 6% and 9% CCP increased the viability of B. lactis in the ice cream and after simulated gastrointestinal processes in all storage periods. These findings imply that CCP is a promising candidate to be used for producing functional ice cream.